Our endangered values : america's moral crisis - Carter, Jimmy ([S.l.] : Simon & Schuster, 2006)
President Jimmy Carter offers a passionate defense of separation of church and state. He warns that fundamentalists are deliberately blurring the lines between politics and religion. As a believing Christian, Carter takes on issues that are under fierce debate -- women's rights, terrorism, homosexuality, civil liberties, abortion, the death penalty, science and religion, environmental degradation, nuclear arsenals, preemptive war, and America's global image.